Análise do processo de constituição do atendimento na delegaciaespecializada de crimes contra a mulher de Belo Horizonte - Camila de Sousa Menezes (2008)
This research aimed to investigate the constitution of the attendance to people at Delegacia Especializada de Crimes Contra a Mulher (Womens Police Station) in Belo Horizonte in the context of application of the law 11.340/2006, also called Lei Maria da Penha. The main objective was to identify and analyse the cases receptioning and directioning practices in the daily work routines of this Police Station, in order to understand the production of the possible paths to the cases, the selection in having access to justice and the reproduction or questioning of violent practices in the daily work routines. In order to achieve this objective, weve raised a historic path of the legislation retated to gender violence and the creation of services for coping with it and, in field research interviews were held and cases accompanied. The ladders were registered in a field book. These practices were analysed in a gender perspective, taking into consideration the discourses they carry and make circulate in the process of constitution of both the attendance and the subjects involved in it.